Liver Biomarkers and Lipid Profiles in Mexican and Mexican-American 10- to 14-Year-Old Adolescents at Risk for Type 2 Diabetes - Ana Cecilia Fernández-Gaxiola; Roxana Valdés-Ramos; Kimberly Fulda; Ana Laura Guadarrama López; Beatriz E. Martínez-Carrillo; Susan F. Franks; Shane Fernando (Journal of Diabetes Research)
Liver enzymes alanine aminotransferase (ALT) and gamma glutamyl transferase (GGT) are markers for type 2 diabetes mellitus (T2DM); alkaline phosphatase is a marker of liver disease. Mexican-American adolescents are disproportionately affected by T2DM, while in Mexico its prevalence is emerging. We assessed liver biomarkers and lipid profiles among Mexican and Mexican-American adolescents 10–14 years old with high/low risk of T2DM through a cross-sectional, descriptive study (Texas n=144; Mexico n=149). We included family medical histories, anthropometry, and blood pressure. Obesity was present in one-third of subjects in both sites. ALT (UL) was higher (p<0.001) in high-risk adolescents (23.5 ± 19.5 versus 17.2 ± 13.4 for males, 19.7 ± 11.6 versus 15.1 ± 5.5 for females), in Toluca and in Texas (26.0 ± 14.7 versus 20.0 ± 13.2 for males, 18.2 ± 13.4 versus 14.6 ± 10.1 for females), as well as GGT (UL) (p<0.001) (18.7 ± 11.1 versus 12.4 ± 2.3 for males, 13.6 ± 5.8 versus 11.5 ± 3.9 for Mexican females; 21.0 ± 6.8 versus 15.4 ± 5.5 for males, 14.3 ± 5.0 versus 13.8 ± 5.3 for females in Texas). We found no differences by sex or BMI. Total cholesterol and HDL were higher among Mexican-Americans (p<0.001). In conclusion, multiple risk factors were present in the sample. We found differences by gender and between high and low risk for T2DM adolescents in all liver enzymes in both sites.